Recalibration of myoelectric control with active learning - Szymaniak, Katarzyna; Krasoulis, Agamemnon; Nazarpour, Kianoush (Frontiers in Neurorobotics, 2022)
Improving the robustness of myoelectric control to work over many months without the need for recalibration could reduce prosthesis abandonment. Current approaches rely on post-hoc error detection to verify the certainty of a decoder’s prediction using predefined threshold value. Since the decoder is fixed, the performance decline over time is inevitable. Other approaches such as supervised recalibration and unsupervised self-recalibration entail limitations in scaling up and computational resources. The objective of this paper is to study active learning as a scalable, human-in-the-loop framework, to improve the robustness of myoelectric control. Active learning and linear discriminate analysis methods were used to create an iterative learning process, to modify decision boundaries based on changes in the data. We simulated a real-time scenario. We exploited least confidence, smallest margin and entropy reduction sampling strategies in single and batch-mode sample selection. Optimal batch-mode sampling was considered using ranked batch-mode active learning. With only 3.2 min of data carefully selected by the active learner, the decoder outperforms random sampling by 4-5% and ~2% for able-bodied and people with limb difference, respectively. We observed active learning strategies to systematically and significantly enhance the decoders adaptation while optimising the amount of training data on a class-specific basis. Smallest margin and least confidence uncertainty shown to be the most supreme. We introduce for the first time active learning framework for long term adaptation in myoelectric control. This study simulates closed-loop environment in offline manner and proposes a pipeline for future real-time deployment.